Konsep Harmonis Dalam Keluarga - Moch. Azis Qoharuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Sakinah family consists of two words, namely family and sakinah. The family is the smallest community, at least consisting of a husband and wife partnership as the main source along with the children born from them. The sakinah family is a calm family, or a peaceful family, happy physically and spiritually, husbands can make their wives happy, wives can make their husbands happy and both are able to educate their children to become children who are transferred and transferred, able to build harmonious brotherhood. with relatives and live in harmony in the neighbourhood, community and state. We can see families who are not confident, for example, families in which there are fights, suspicions between partners, and even the potential for conflict that leads to divorce. Distrust is one aspect that makes the Sakinah family fail to happen. For example, a couple suspects each other, there are parties or people who shake up the household or the wife's resistance to her husband. According to Islam, the law against husbands is certainly something that must be known by wives to maintain sakinah in the family.